A Review on Management of Vataja Shirorog W.S.R. to Tension type Headache through Dashmooladi Siddha Ksheerdhara and Oral Administration - Singh, Surabhi; Kumar, Ajay; Singhal, Tina (International Research Journal of Ayurveda & Yoga, 2024)
It is sad and known to everybody that in today’s era, it is difficult to maintain one’s mental health. A happy mind can accomplish anything but with a busy, competitive, and demanding life, earning bread and butter has deteriorated one’s mindset. Today’s lifestyle change, i.e., irregular food habits, suppression of natural urges, lack of proper sleep, and less time for relaxation, has increased incidences of many diseases. Due to complexity, diversity, and range of root causes of mental health and little awareness about healthy mind among people, it becomes challenging to diagnose the problem. In Ayurveda, mind contemplates to be a bridge between indriyas and indriyarthas. If the mind is unhealthy, it will surely reflect upon the body. Insomnia, insanity, tension-type headache, office headache, depression, schizophrenia, stress, and anxiety have now become very common. Fortunately, in Ayurveda, there are various lines of treatments such as Satva avajaya chikitsa, Daivya vyapasraya chikitsa, Adravyabhoot chikitsa, Yukti vyapasraya chikitsa, Achar rasayan, Yoga, and pranayama followed by proper diet and also Panchakarma therapies such as nasya and shirodhara with medicated oil seems quite effective. Shirodhara can be performed using a variety of herbs including takra, ksheer, kwath, etc. It involves continually and rhythmically pouring liquid over the forehead from a specified height for a set amount of time. The liquid depends on what disease is being treated. Shirodhara also involves a head massage. It is thought to be a good relaxing procedure for mind.